Financial markets in the Southern African development community: the harmonisation and approximation of commercial laws - Henning, J.; Du Toit, S. (Faculty of Law, University of the Free State, 2003)
The free flow of capital has been identified as a critical factor in the process of reducing poverty in the SADC region, along with the lowering of trade barriers. While the trade protocols have been adopted and much has been made of the harmonisation of stock exchange listing requirements and central banking regulation, it is an effort at harmonising corporate law that is noticeably absent. This article focuses on the harmonisation of business law including the supporting financial markets and the process of corporate law reform in South Africa, Botswana and Zimbabwe.

Die SAOG is nie huiwerig om kennis te neem van harmoniseringsmodelle in ander streke nie. Dit is reeds voorgestel dat die SAOG die benadering of kombinasie van benaderings volg wat die streek die beste sal pas. Die vrye beweging van kapitaal tesame met die vermindering van handelsbeperkinge is geïdentifiseer as 'n kritieke faktor in die verligting van armoede in die streek. Terwyl handelsprotokolle aanvaar is en klem gelê word op die harmonisering van effektebeursnoteringsvereistes en die regulering van sentrale banke, ontbreek die harmonisering van korporatiewe reg. Hierdie artikel fokus op die harmonisering van kommersiële reg insluitend ondersteunende finansiële markte en die proses van korporatiewe regshervorming in Suid-Afrika, Botswana en Zimbabwe.